Academic Senate Minutes 2021-02-18 - Academic Senate:::::::::
Approval of Agenda - Items added: Priority Registration application; Resolution on Faculty Participation in Commencement from S&F - Approved. Minutes of 3/8/18 – Approved. Chair Report. President Report. Priority Registration Application: Supplemental Instruction Leaders - Instructional Student Assistants – Approved. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. From S&F: Resolution regarding Faculty Participation – Approved for Senate agenda. Discussion of Sonoma Valley Room for Senate meetings. Update on LMS project. EPC Report. CFA Report. Associated Students Report. Senate agenda approved.